1998
DOI: 10.3327/jnst.35.190
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Radioactive Strontium Distribution Coefficient by Analyzing Background Stable Strontium.

Abstract: A new method of evaluating the distribution coefficient ( K d ) of radioactive Sr was examined. The method is based on the measurement of the solid-liquid concentration distribution ratio ( R d )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Herein, the reactive solid phase means the part of the solid that is involved with the sorption. In a previous paper [12], it was found that the f d value of strontium (Sr) agreed with the K d value of Sr obtained from batch methods at the same liquid-phase stable Sr concentration, indicating that the K d of Sr can be evaluated by the f d of Sr.…”
Section: Introductionmentioning
confidence: 65%
“…Herein, the reactive solid phase means the part of the solid that is involved with the sorption. In a previous paper [12], it was found that the f d value of strontium (Sr) agreed with the K d value of Sr obtained from batch methods at the same liquid-phase stable Sr concentration, indicating that the K d of Sr can be evaluated by the f d of Sr.…”
Section: Introductionmentioning
confidence: 65%